Deeply responsible business a global history of values-driven leadership - Jones, Geoffrey 1952- (Harvard University Press, 2023)
Corporate social responsibility has entered the mainstream, but what does it take to run a successful purpose-driven business? A Harvard Business School professor examines leaders who put values alongside profits to showcase the challenges and upside of deeply responsible business.For decades, CEOs have been told that their only responsibility is to the bottom line. But consensus is that companies-and their leaders-must engage with their social and environmental contexts. The man behind one of Harvard Business School's most popular courses, Geoffrey Jones distinguishes deep responsibility, which can deliver radical social and ecological responses, from corporate social responsibility, which is often little more than window dressing.Deeply Responsible Business offers an invaluable historical perspective, going back to the Quaker capitalism of George Cadbury and the worker solidarity of Edward Filene.